Right Place, Right Time: Análise Semiótica de uma Fanfic. - Leal, Letícia Cardoso (Universidade Federal do Tocantins, 2024)
This paper discusses one of the productions of one of these genres that emerge from digital culture, fanfic, which became popular in the 1960s and 1970s through Science Fiction (SF) fanzines, especially Star Trek fanzines. Fanfic is understood as fan-to-fan writing that aims to provide continuity or an alternative ending to the characters of their favorite universe. The fanfiction Right Place, Right Time, a fanfic by Amanda Maloes about the singer Shawn Mendes, was defined as the object of study of this work. The objective of this work will be to analyze the processes and elements of figurativeness of the central characters, in addition to seeking to interpret the “enunciation marks” chosen in order to give veracity to the narrative. The methodology of this work takes place in a bibliographical and documental way, focusing on the semiotic analysis of the French line. For that, we resorted to studies proposed by Barros (1999; 2005), Fiorin (1996), Greimas and Courtés (1979), among others. Despite the variety of themes and styles, we sought to observe what may be a recurrence of writing in the genre, close to what Barros (1999) calls pink literature.